Discussion of Katharina Kraus’ Kant’s Ideas of Reason - Tizzard, Jessica (Con-Textos Kantianos. International Journal of Philosophy, 2025)
In this discussion of Katharina Kraus’ Cambridge Element Kant’s Ideas of Reason, I explore the interpretive upshot of her perspectivalist approach to the regulative use of ideas in Kant’s theoretical philosophy. After briefly summarizing her basic framework, I pose a series of questions about how her position could be interpreted as a form of modest noumenalism, focusing on the claim that a grounding relation to unconditioned reality is needed to maintain an objective criterion of truth. This leads to some brief reflections on the nature of objectivity in Kant’s broader philosophical system. I conclude by pointing out the advantages of her twofold approach to the regulative use of ideas, which serve both semantic and epistemic functions, and suggest this distinction is also essential to understanding the use of ideas in Kant’s practical philosophy.